Pengembangan Model Pembelajaran Adaptif Berbasis The Forgetting Curve untuk Meningkatkan Retensi Konsep Spasial dalam Pembelajaran Geografi - Lalan Rojulan; Siti Sanisah; Arif Arif (Universitas Hamzanwadi, 2026)
The main challenge faced in Geography learning is memory decline, especially regarding spatial concepts that are often complex and abstract. The Forgetting Curve cognitive theory explains that human memory tends to decline over time if there is no organized repetition. This study aims to create an adaptive learning model based on the Forgetting Curve to improve student retention of spatial concepts in Geography. The method used in this study was a Research and Development approach with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The research subjects were 35 11th-grade students at MA Nurul Ittihad. Research data were obtained through test instruments to measure spatial knowledge retention, questionnaires about student perceptions, and observation sheets to assess the implementation of the model. The results of the study indicate that the adaptive learning model based on The Forgetting Curve has a very high feasibility level with an expert validation score of 87.9%. The model has also been proven to be practical, as demonstrated by an implementation success rate of 91.4% and student engagement of 86.2%. Cohen's d value of 3.80 indicates the model's high effectiveness in improving learning outcomes. The model is also effective in improving students' spatial concept retention, as reflected in the increase in pretest scores (61.04) to 77.75 (posttest), and remains high (73.91) on the delayed test. These findings confirm that implementing adaptive learning based on The Forgetting Curve can strengthen students' long-term retention of spatial concepts in Geography learning.